Labour market fluctuations: An RBC model for emerging countries - Sevgi Coskun (Central Bank Review (CBR), 2019)
In this paper, we examine the labour market properties of business cycle fluctuations for a group of 15 emerging market economies (EMEs) and the US using annual data from 1970 to 2013. We find that on average, the hours worked and employment volatility (relative to output volatility) are lower, while the volatility of productivity and wages are 2–3 times higher in EMEs compared to the US. We then assess the performance of a standard RBC model and an augmented RBC model with capacity utilization, investment adjustment cost and indivisible labour with temporary and permanent productivity shocks to explain labour market facts observed in the data. We find that these models fail to explain labour market fluctuations in the business cycles of these countries, but the model with investment adjustment cost improves the performance of relative volatility of wages and hours, as well as the cyclicality of hours, compared to the standard RBC model. Lastly, we investigate the cyclical properties of the labour wedge and find that the total labour wedge (relative to output volatility) is more volatile over the business cycle in emerging economies (1.72) compared to the US (0.95). Further, fluctuations in the total labour wedge reflect the ones in the household component rather than the firm component of the wedge in EMEs and the US.
Keywords: E31; E32; E52; F41; O50; 330; Labour market; Emerging market economies; Real business cycle model; Labour wedge